2014
DOI: 10.1177/156482651403500105
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin Intake and 5-Year Blood Pressure Change in Chinese Adults: Interaction with Hypertensive Medication

Abstract: Background. One previous large cross-sectional study across four countries suggests that riboflavin intake may be inversely associated with blood pressure.Objective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In a large, observational study of 6076 Irish adults, the low or deficient biomarker status of riboflavin was about 30% and exacerbated the genetic risk of hypertension associated with the MTHFR 677TT genotype [37]. In a five-year cohort study of Chinese adults, a higher riboflavin intake was found to be inversely associated with a change in systolic blood pressure [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large, observational study of 6076 Irish adults, the low or deficient biomarker status of riboflavin was about 30% and exacerbated the genetic risk of hypertension associated with the MTHFR 677TT genotype [37]. In a five-year cohort study of Chinese adults, a higher riboflavin intake was found to be inversely associated with a change in systolic blood pressure [16].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of public health relevance have related to the importance of riboflavin as a factor in protecting against CVD, cancers, and in vision [15,16]. Yet, its relationship with mortality has not been investigated, unlike other vitamin B family members.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, considering the high content of bioactive compounds and phytochemicals in plant foods [160], a personalized nutrition (Figure 1) should take into account potential food-drug interactions in veterans who are in treatment for comorbidities. In agreement, dietetic interventions based on personalized dietary advice have also been suggested for old subjects [161], in order to avoid potential food-drug interactions [162][163][164][165][166][167][168][169][170]. In particular, the effect of high-protein, low-carbohydrate diets on warfarin efficacy should be taken into consideration [169,170].…”
Section: Healthy Diet For Veteransmentioning
confidence: 99%
“…To our knowledge, all human studies on riboflavin and bone health were conducted so far in Western countries, where riboflavin intake is generally higher (average intake ranged from 1.5 to 2.0 mg/d) ( 14 , 16 , 17 ). However, the mean dietary intake of riboflavin in Chinese population is around 0.80 mg/d ( 18 ), which is lower than the recommended dietary intake (1.2–1.4 mg/d) and there is a relatively high prevalence of osteoporosis in China. However, the evidence for the association between riboflavin intake and BMD is lacking in Chinese population.…”
Section: Introductionmentioning
confidence: 99%